(untitled) (Journal of Management & Business, 2025)
This research aims to understand the relationship between economic complexity and the circular economy in different scenarios through a comprehensive literature review. The results emphasize the crucial role of economic complexity in sustainable development and the effectiveness of the circular economy. Studies indicate the importance of policies and strategies to promote the transition to more circular practices, considering the diversity of national contexts and encouraging innovation and collaboration between sectors. The analysis reveals that countries with higher economic complexity tend to have more robust frameworks for implementing circular economy principles. This includes advanced technological capabilities, diversified industrial bases, and strong institutional support. By examining various case studies, the research highlights successful examples of circular economy initiatives driven by economic complexity. These initiatives often result in increased resource efficiency, reduced environmental impact, and enhanced economic resilience. Moreover, the findings suggest that fostering economic complexity can accelerate the adoption of circular economy practices. This requires targeted policy interventions, investment in education and research, and the promotion of public-private partnerships. Encouraging a culture of continuous learning and adaptation is also essential to navigate the challenges and opportunities presented by the circular economy. Overall, the study underscores the interconnectedness of economic complexity and circular economy as pivotal elements in achieving sustainable development goals.